2009
DOI: 10.1681/asn.2008090954
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preventive Health Care with Atherosclerotic Heart Disease and Mortality in CKD

Abstract: Chronic kidney disease (CKD, stages 1 to 4) affects approximately 13.1% of United States adults and leads to ESRD, cardiovascular disease, and premature death. Here, we assessed adherence to a subset of Kidney Disease Outcomes Quality Initiative preventive health care guidelines and identified associations between adherence and incident atherosclerotic heart disease (ASHD). Using the Medicare 5% data set, 1999 to 2005 (about 1.2 million patients per year), we created 3-yr rolling cohorts. We classified CKD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Two smaller studies from Poland and Greece showed similar results (9,10). The lower risk of death is consistent with other influenza vaccine studies in the chronic kidney disease and ESRD populations (11,12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two smaller studies from Poland and Greece showed similar results (9,10). The lower risk of death is consistent with other influenza vaccine studies in the chronic kidney disease and ESRD populations (11,12).…”
Section: Discussionsupporting
confidence: 89%
“…Despite recommendations from society guidelines, only 19% of patients had claims for influenza vaccination within the first year after transplant in this cohort. This rate is lower than reported in the aforementioned chronic kidney disease and ESRD populations using similar methodology (11,12). Multiple surveys and observational studies have previously commented on the low rate of vaccination in solid-organ-transplant recipients internationally (13).…”
Section: Discussionmentioning
confidence: 65%
“…We limited our analysis to a single year and did not include certain potential longer-term benefits of influenza vaccination such as lowered heart disease risk that has been described in previous studies. 48 Our model tried to represent the average HD patient. While sensitivity analyses explored the effects of some variation, they cannot capture the full possible extent of variability.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CKD also associates with various complications and their costs, including cognitive impairment, 14,15 cardiovascular disease, [16][17][18][19] sudden death, 20 abnormal mineral metabolism, [21][22][23] bone fracture, 24 vascular ossification 25 and remodeling, 26 postoperative mortality, 27 risk of AKI, 28,29 cancer, 30 and patient safety 31 just to mention a few. No one is sure all these risks are shared equally across the spectrum of patients with varying degrees of CKD.…”
mentioning
confidence: 99%
“…Early efforts to map complications with albuminuria or levels of estimated GFR suggest differential associations. 32 There also are issues with prevention, 16 pre-ESRD access, socioeconomics, and race that affect quality of care, [33][34][35] and save for piecemeal, we cannot interrogate these concerns thoughtfully without establishing a larger pool of valid patients for longitudinal surveillance.…”
mentioning
confidence: 99%